Pre- and post-operative antibiotics in conjunction with cytoreductive surgery and heated intraperitoneal chemotherapy (HIPEC) should be considered for pseudomyxoma peritonei (PMP) treatment. Issue 9 (September 2019) - Merrell, D. Scott; McAvoy, Thomas J.; King, Mary Caitlin; Sittig, Michelle; Millar, Eugene V.; Nieroda, Carol; Metcalf, Jessica L.; Blum, Faith C.; Testerman, Traci L.; Sardi, Armando
Abstract: Pseudomyxoma peritonei (PMP) is a subtype of peritoneal carcinomatosis that is traditionally treated by cytoreductive surgery (CRS) followed by hyperthermic intraperitoneal chemotherapy (HIPEC). A growing body of evidence suggests that microbes are associated with various tumor types and have been found in organs and cavities that were once considered sterile. Prior and ongoing research from our consortium of PMP researchers strongly suggests that bacteria are associated with PMP tumors. While the significance of this association is unclear, in our opinion, further research is warranted to understand whether these bacteria contribute to the development, maintenance and/or progression of PMP. Elucidation of a possible causal role for bacteria in PMP could suggest a benefit for supplementation of antibiotics to current treatment protocols.